2014
DOI: 10.5713/ajas.2014.14209
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism, Genetic Effect and Association with Egg Production Traits of Chicken Matrix Metalloproteinases 9 Promoter

Abstract: Matrix metalloproteinases (MMP) are key enzymes involved in cell and tissue remodeling during ovarian follicle development and ovulation. The control of MMP9 transcription in ovarian follicles occurs through a core promoter region (−2,400 to −1,700 bp). The aim of this study was to screen genetic variations in the core promoter region and examine MMP9 transcription regulation and reproduction performance. A single cytosine deletion/insertion polymorphism was found at −1954 C+/C−. Genetic association analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The yolk in the SWF and F1 follicles was carefully removed with a syringe and a 25-gauge needle before snap frozen. The granulosa cells were isolated as described previously [ 8 , 9 ]. In brief, the second largest (F2), third largest (F3), and fourth largest (F4) follicles were isolated and punctuated with sterile needles to remove the yolk.…”
Section: Methodsmentioning
confidence: 99%
“…The yolk in the SWF and F1 follicles was carefully removed with a syringe and a 25-gauge needle before snap frozen. The granulosa cells were isolated as described previously [ 8 , 9 ]. In brief, the second largest (F2), third largest (F3), and fourth largest (F4) follicles were isolated and punctuated with sterile needles to remove the yolk.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of Bacillus-based preparations have been found to promote growth, feed utilization and digestive health, subsequently, registered as probiotics for animal feed [51][52][53]. Egg production performance determines the economic benefits in laying hen production system owing to its effects on productivity [54]. Similar to our study, geese fed with 10 9 cfu g −1 Bacillus subtilis can increase growth performance and leg muscle weight (p < 0.05) because of its modulating the intestinal microflora ecology of the animal [55].…”
Section: Bacillus Amyloliquefaciens Supplemented In Feed For Wanxi White Goosementioning
confidence: 99%
“…Low expression of genes enriched in the ECM-receptor interaction pathway in this study suggests slow and perhaps more organized growth of the prehierarchical follicles in the crossbred hens ( Zhou et al, 2020 ). Specifically, 2 MMPs ( MMP9 and MMP10 ) with underdominance in the crossbred laying hens were linked to the degradation and resynthesis of extracellular matrix, the ovarian cycle, follicle development, and ovulation ( Oktay et al, 2000 ; Zhu and Jiang, 2014 ; Liu et al, 2018 ). High expression of these genes also promotes the rapture of ovarian follicles ( Liu et al, 2018 ) and a genome wide association study identified SNPs in the promoter region of MMP9 in chickens characterized by high egg production ( Zhu and Jiang, 2014 ).…”
Section: Discussionmentioning
confidence: 99%